Dorko the magnificent - Beaty, Andrea (Amulet Books, 2013)
Robbie Darko is an old-school, pull-a-rabbit-out-of-your-hat-style magician, but despite his best efforts, something always goes wrong with his tricks until crotchety Grandma Melvyn moves in and teaches him something about the true meaning of magic.